2008
DOI: 10.1111/j.1365-2222.2008.03089_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Response by Anu Huurre, on behalf of the NAMI (Nutrition, Allergy, Mucosal Immunology and Intestinal Microbiota) research group

Abstract: With great interest, we have read the article by Huurre et al. [1] reporting on the impact of maternal atopy and probiotic supplementation during pregnancy on infant sensitization. We would like to comment on some of the results of this trial.First, the authors found an increased risk of sensitization in infants with allergic mothers breastfeeding over 6 months or exclusively breastfeeding over 2.5 months. Therefore, they conclude that breastfeeding in atopic mothers is a risk factor for sensitization in infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For the combined prenatal/postnatal probiotic studies, there was a significant reduction in the cumulative incidence of eczema and/or IgE-associated eczema in six of the nine published RCTs (Kalliomaki et al, 2001b; Kukkonen et al, 2007; Wickens et al, 2008; Niers et al, 2009; Dotterud et al, 2010; Kim et al, 2010) by age 2 years. No such effects were reported in the other three studies (Abrahamsson et al, 2007; Huurre et al, 2008; Kopp et al, 2008). Interestingly, of these nine prenatal/postnatal studies, a beneficial effect was found in three of five studies that used LGG with or without other probiotics (LGG (Kalliomaki et al, 2001b); L. rhamnosus LC705, B. breve Bb99, and Propionibacterium freudenreichii + the prebiotic GOS (Kukkonen et al, 2007); LGG, L. acidophilus La-5 and B. lactis Bb12 (Dotterud et al, 2010).…”
Section: Evidence For the Clinical Effects Of Probiotics In Allergic mentioning
confidence: 83%
See 2 more Smart Citations
“…For the combined prenatal/postnatal probiotic studies, there was a significant reduction in the cumulative incidence of eczema and/or IgE-associated eczema in six of the nine published RCTs (Kalliomaki et al, 2001b; Kukkonen et al, 2007; Wickens et al, 2008; Niers et al, 2009; Dotterud et al, 2010; Kim et al, 2010) by age 2 years. No such effects were reported in the other three studies (Abrahamsson et al, 2007; Huurre et al, 2008; Kopp et al, 2008). Interestingly, of these nine prenatal/postnatal studies, a beneficial effect was found in three of five studies that used LGG with or without other probiotics (LGG (Kalliomaki et al, 2001b); L. rhamnosus LC705, B. breve Bb99, and Propionibacterium freudenreichii + the prebiotic GOS (Kukkonen et al, 2007); LGG, L. acidophilus La-5 and B. lactis Bb12 (Dotterud et al, 2010).…”
Section: Evidence For the Clinical Effects Of Probiotics In Allergic mentioning
confidence: 83%
“…While a paucity and evidence – mainly inconclusive – exists for the use of probiotics in the treatment of allergic disease, several clinical trials have been successful in the use of probiotics for the prevention of allergic disease. At present, a total of 14 randomized controlled trials evaluating various probiotics have been reported, mostly involving infants of families with a history of allergic disease (summarized in Table 4; Kalliomaki et al, 2001b; Rautava et al, 2006; Abrahamsson et al, 2007; Kukkonen et al, 2007; Taylor et al, 2007; Huurre et al, 2008; Kopp et al, 2008; Wickens et al, 2008; Niers et al, 2009; Soh et al, 2009; West et al, 2009; Dotterud et al, 2010; Kim et al, 2010; Boyle et al, 2011). …”
Section: Evidence For the Clinical Effects Of Probiotics In Allergic mentioning
confidence: 99%
See 1 more Smart Citation